2019
DOI: 10.7717/peerj.7294
|View full text |Cite
|
Sign up to set email alerts
|

Shoot and root traits of summer maize hybrid varieties with higher grain yields and higher nitrogen use efficiency at low nitrogen application rates

Abstract: Breeding high-yielding and nitrogen-efficient maize (Zea mays L.) hybrid varieties is a strategy that could simultaneously solve the problems of resource shortages and environmental pollution. We conducted a 2-year field study using four nitrogen application rates (0, 150, 225, and 300 kg N hm−2) and two maize hybrid varieties (ZD958 and QS101) to understand the plant traits related to high grain yields and high nitrogen use efficiency (NUE). We found that ZD958 had a higher grain yield and nitrogen accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…The application of UCZ together with N protected the photosynthetic system and obtained higher grain yields. Previous studies also showed that the application of UCZ together with N increased the grain yield in various crops by reducing the lodging rate and enhancing the photosynthetic performance (Wang et al 2009(Wang et al , 2015aSu et al 2019). In addition, our previous studies demonstrated that UCZ increased the grain yield in maize with a medium plant population density by reducing leaf senescence in the bottom layer.…”
Section: Effects Of Ucz and N Fertilization On Grain Yield Of Maize Cmentioning
confidence: 71%
“…The application of UCZ together with N protected the photosynthetic system and obtained higher grain yields. Previous studies also showed that the application of UCZ together with N increased the grain yield in various crops by reducing the lodging rate and enhancing the photosynthetic performance (Wang et al 2009(Wang et al , 2015aSu et al 2019). In addition, our previous studies demonstrated that UCZ increased the grain yield in maize with a medium plant population density by reducing leaf senescence in the bottom layer.…”
Section: Effects Of Ucz and N Fertilization On Grain Yield Of Maize Cmentioning
confidence: 71%
“…Previous studies showed that both grain protein content GPC and grain yield (GY) can be increased by N fertilizer simultaneously under low to medium N rate (0-200 kg N ha -1 ), but grain protein content (GPC) was continuously increased with no further increase in GY under high N rate (210-280 kg N ha -1 ). In China, the N application rate has been generally much higher than the recommended dose of 280 kg N ha -1 in soft wheat production for higher grain yield GY (Su et al 2019). Reducing N rate can signi cantly decrease GPC and wet gluten content (WGC) of soft wheat, which help to form softer dough and produce crisper biscuits (Zheng et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Modern varieties with deeper root distribution can increase yield under low N conditions [10]. A strong root system is an important factor for high yields [11].…”
Section: Introductionmentioning
confidence: 99%
“…The RSA of modern maize varieties in China is characterized by "horizontal contraction and vertical extension", which is more suitable for planting at a higher N level [17]. Response to N fertilizer varies with genotype, the yield and root biomass of maize varieties with high N efficiency are higher than those with low N efficiency [10,18].…”
Section: Introductionmentioning
confidence: 99%